Healthcare utilization in patients with higher-risk MDS/low-blast count AML treated with azacitidine in the 'real-world'. Issue 6 (11th May 2020) - Mozessohn, Lee; Cheung, Matthew C.; Mittmann, Nicole; Earle, Craig C.; Liu, Ning; Buckstein, Rena
Abstract: Despite the adoption of azacitidine (AZA) in higher-risk MDS/low-blast count AML, limited 'real-world' data on resource utilization and toxicity exist. We linked the Ontario AZA-MDS registry to population-based administrative databases. Among 877 patients in the registry, 705 (80.4%) had at least one emergency department (ED) visit, 290 (33.1%) had an ED visit during their first cycle and 680 patients (77.5%) had at least one hospitalization (mean length 17.7 days, 95% CI 16.3–19.1). Older age, rurality, non-response to AZA, transfusion dependence, IPSS score, and greater comorbidity were independent predictors of increased ED visits; while greater comorbidity, non-response to AZA, and transfusion dependence were associated with longer hospitalization. When restricted to receiving ≥3 cycles, hospitalization during the first cycle was associated with increased risk of death. Our analysis of 'real-world' patients treated with AZA demonstrates significant healthcare utilization and increased risk of death for patients hospitalized during their first cycle. These results will inform patients/providers about 'real-world' toxicities of AZA.